Echa awangardy — przypadek Juliana Kornhausera - Piotrowska-Grot, Magdalena (Zagadnienia Rodzajów Literackich, 2024)
This article examines the influence of avant-garde poetics on the poetry of one of the representatives of the New Wave — Julian Kornhauser. The text consists of two main parts. The first part explores how the creators of the New Wave perceived the avant-garde and what they aimed to achieve, and provides definitions of the avant-garde as an aesthetic phenomenon to broaden the research perspective and specify the correlation between the poetry of the New Wave and the historical avant-garde. The second part of the sketch consists of a collection of microanalyses of Julian Kornhauser’s poetic texts, which refer to avant-garde linguistic and aesthetic experiments. In the selected poems, we find, beyond intertextual references, plays with the works of Rilke, the Futurists, or Miron Białoszewski. This compilation aims to help answer whether (and to what extent) Julian Kornhauser is a post/neo-avant-garde poet. It also highlights the broad circles of cultural dialogues, which this creativity invites us to follow. This part also demonstrates the variety of forms of these references — from cryptic quotations through imitation (parody) of poetics to giving avant-garde poetic experiments new semantic and formal qualities. Julian Kornhauser appears as a descendant of the avant-garde — conscious of its power, constant presence, variability, and the impossibility of many of its demands. He is its disobedient ward, using its demands only partially, reshaping their original form. The avant-gardism of Kornhauser’s poetry, or rather, the inevitability, or, as Jan Sowa wrote, the persistence of the avant-garde, is manifested primarily at the intersection of poetry (prose) and reality, creating a new quality that allows for their correlation and coexistence.